PENGARUH STRUKTUR AKTIVA, PROFITABILITAS DAN PERTUMBUHAN PENJUALAN TERHADAP STRUKTUR MODAL PADA PERUSAHAAN FOOD AND BEVERAGE DI BURSA EFEK INDONESIA PERIODE 2015-2020 - Haloho, Befriana Utami; Silalahi, Donalson (UNIKA Santo Thomas, 2023)
This study aims to determine and explain the effect of asset structure, profitability (return on equity) and sales growth on the capital structure of food and beverage companies on the Indonesia Stock Exchange for the 2015-2020 period. To achieve this goal, a research was conducted using secondary data taken from the Indonesian stock exchange with website: www.idx.co.id. By using purposive sampling, the research sample was 14 companies and used multiple linear regression as an analytical tool. The results show that: First, asset structure has a positive and significant effect on capital structure, profitability (return on equity) has a negative and insignificant effect on capital structure and sales growth has a positive and significant effect on capital structure in food and beverage companies listed on the Indonesian Stock Exchangefor the 2015-2020 period. Second, variations in asset structure, profitability (return on equity) and sales growth are able to explain variations in capital structure by 21.9 percent.